1994
DOI: 10.1007/bf01229069
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of asialoglycoprotein receptor synthesis by inflammation-related cytokines in HepG2 cells

Abstract: The asialoglycoprotein receptor (AGPR) is responsible for the catabolism of acute phase proteins. The effects of inflammation-related cytokines on the expression of AGPR were investigated in HepG2 cells derived from a human hepatoblastoma cell line. Binding studies, using a [125I]-labeled asialo-orosomucoid ligand, revealed that AGPR numbers on cell surfaces were increased by interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor (TNF). In cells treated with IL-1, IL-6, or TNF, immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Blood samples (400 mL) were drawn from the carotid artery before and at 10,20,25,30,35,40, and 50 min after injection. After 50 min, urine was collected from the bladder.…”
Section: Gecmentioning
confidence: 99%
“…Blood samples (400 mL) were drawn from the carotid artery before and at 10,20,25,30,35,40, and 50 min after injection. After 50 min, urine was collected from the bladder.…”
Section: Gecmentioning
confidence: 99%
“…The expression of ASGPRs appears to be regulated at both the transcriptional and posttranscriptional levels, and is controlled by the cell cycle as well as various other factors including biotin and the cytokines [13][14][15][16][17]. In addition to these factors, the number of living hepatocytes is also positively correlated with 99m Tc-GSA binding activity.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 It has also been reported that they stimulate hepatocytes to synthesize AGPR. 8 Therefore, changes in AGPR expression and function may conceivably be involved in the pathogenesis of alcoholic liver diseases.…”
Section: Mechanisms Of Ethanol-induced Impairment In Asialoglycoprotementioning
confidence: 99%